LONG-TERM OUTCOMES OF PHARMACOLOGICAL VERSUS SURGICAL TREATMENT IN WOMEN WITH ENDOMETRIOSIS: IMPACT ON RECURRENCE AND QUALITY OF LIFE — A REVIEW ARTICLE - Marzec, Urszula; Giza, Agnieszka; Rajca, Eliza; Cyrkler, Aleksandra; Cieślak, Natalia; Giza, Paulina; Chodkowska, Agata; Czyżak, Kamila; Dąbek, Karol; Wymoczył, Karolina (International Journal of Innovative Technologies in Social Science, 2026)
Background: Endometriosis is a chronic inflammatory estrogen-dependent disease affecting approximately 10% of women of reproductive age. Although there have been significant advancements in diagnosis and management, the recurrence and sustained impaired quality of life (QoL) constitute a serious challenge for clinical care. Treatments aim at pharmacological inhibition and surgical excision, but long-term comparative outcomes are controversial. Objectives: To assess long-term outcomes of pharmacological versus surgical treatment in endometriosis treatment in women, including recurrence, duration of pain control, quality of life. Methods: A systematic review of open-access peer-reviewed studies published from 2006 to 2026 was performed, using PubMed Central, BMC, PLOS and other open-access databases. The inclusion criteria included randomized controlled trials (RCTs), systematic reviews, meta-analyses, and large cohort studies with ≥12 month follow-up. The included studies included were made up of thirty-five eligible studies. Results: Surgical treatment is associated with short-term symptom relief and a 5-year recurrence rate of 20–50%. Drug interventions (COCs, progestins, GnRH analogues/antagonists) provide analgesia but have a high recurrence rate on discontinuation. The incidence of the recurrence is markedly decreased as a result of combined postoperative hormonal treatment. QoL is improved in both modalities; sustained benefit associated with recurrence prevention and improved QoL is evident in each modality. Conclusions: There is no absolute cure for either modality alone. There is an indication for personalized interventions with treatment and individualized approach, surgical and long-term hormonal suppression leading to the most durable results in patients.